DINAMIKA ULUMUL QUR’AN: SEJARAH, TOKOH, DAN ARAH PEMBARUAN KONTEMPORER - Muhammad Patri Arifin (Program Studi Sejarah Peradaban Islam, 2024)
Ulum al-Qur’an, as a collection of disciplines concerned with various aspects of the Qur’an, has undergone a long process of development throughout Islamic history. This development has passed through several phases, each characterized by its own distinctive features, beginning with the period of oral transmission (musyafahah wa al-talaqqi), followed by the codification phase (tadwin), and continuing into the modern and contemporary eras. Over time, the study of Ulum Qur’an expanded significantly, giving rise to several independent branches of knowledge. One of the most prominent is Qur’anic exegesis (tafsir), which has experienced substantial growth in terms of methodology, approaches, and interpretive trends. This chapter seeks to present a systematic overview of the development of Ulum Qur’an, starting from its early stages before codification and extending to its modern and contemporary developments. The discussion covers not only the contributions of Middle Eastern scholars but also the development of Qur’anic studies in Indonesia and Orientalist perspectives on Qur’anic sciences. In addition, brief biographies and major works of influential scholars are highlighted to provide readers with a broader understanding of the historical and intellectual development of Ulum Qur’an.